Information literacy skills of health professions students in assessing YouTube medical education content - Pearlman, Orianne; Konecny, Lynda Tierney; Cole, Matthew (Frontiers in Education, 2024)
YouTube is a popular social media video platform used by health professions students for medical education. YouTube videos vary in quality, and students need to be able to evaluate and select highquality videos to supplement their learning. Evaluating the quality of YouTube videos is an essential information literacy skill, and the Association of College & Research Libraries updated the framework of information literacy to include collaborative platforms such as YouTube. Research is needed to understand and explore the information literacy proficiency of students in the health professions who are using YouTube videos as learning resources. This exploratory expert-novice study investigated the information literacy proficiency of students in evaluating the quality of medical education YouTube videos. Students (n = 89) and experts (n = 23) evaluated three preselected medical education YouTube videos of varying quality using the Medical Quality Video Evaluation Tool (MQ-VET). Results of two-way mixed repeated measures ANOVA found experts assigned significantly lower ratings to low-and medium-quality videos compared to students. In other words, students were less information proficient in selecting videos due to overrating source credibility, education quality, and production quality, along with having lower expectations and finding videos more useful. The tendency of students to overrate lower-quality videos raises concerns about their selection of educational content outside structured learning environments. If students select videos to watch outside the classroom, they could unintentionally learn medical skills from low-quality videos. These insights suggest a need for teachers to select only high-quality videos for students and for more focused curricular strategies to enhance students' abilities in critically assessing YouTube resources for medical education.